In-vitro effect of vaginal lactobacilli against group B Streptococcus. (November 2019) - Marziali, Giacomo; Foschi, Claudio; Parolin, Carola; Vitali, Beatrice; Marangoni, Antonella
Abstract: Streptococcus agalactiae (GBS) is a leading cause of infection during pregnancy, preterm birth and neonatal infection, with a significant clinical and socio-economic impact. To prevent maternal GBS vaginal colonization, new antibiotic-free approaches, based on lactobacilli probiotics, are advisable. The aim of this study was to assess the anti-GBS activity of 14 vaginal Lactobacillus strains, belonging to different species ( L. crispatus, L. gasseri, L. vaginalis ), isolated from healthy pre-menopausal women. In particular, we performed 'inhibition' experiments, evaluating the ability of both Lactobacillus cells and culture supernatants in reducing Streptococcus viability, after 60 min contact time. First, we demonstrated that the acidic milieu, produced by vaginal lactobacilli metabolism, is crucial in counteracting GBS growth in a pH-dependent manner. Experiments with organic/inorganic acid solutions confirmed the strict correlation between pH levels and the anti-GBS activity. GBS was more sensitive to lactic acid than to hydrochloric acid, indicating that the presence of H + ions is necessary but not sufficient for the inhibitory activity. Moreover, experiments with Lactobacillus pH-adjusted supernatants led to exclude a direct role in the anti-GBS activity by other bioactive molecules. Second, we found that only a few Lactobacillus strains were able to reduce Streptococcus viability by means of cell pellets. The anti-GBS effect displayed by Lactobacillus cells was related to the their ability to interact and aggregate with Streptococcus cells. We found that the anti-GBS activity was retained after methanol/proteinase K treatment, but lost after lysozyme exposure of Lactobacillus cells. Therefore, we supposed that non-proteinaceous components of Lactobacillus cell wall could be responsible for the anti-GBS activity. In conclusion, we identified specific Lactobacillus strains able to interfere with GBS viability by multiple strategies and we elucidated some of the mechanisms of action. These strains could serve as probiotic formulations for the prevention of GBS vaginal colonization. Highlights: Vaginal Lactobacillus reduce Streptococcus agalactiae viability by multiple strategies. The acidic milieu produced by Lactobacillus is crucial for the anti-GBS activity. GBS is more sensitive to lactic acid than to hydrochloric acid. The anti-GBS effect displayed by Lactobacillus is at least in part related to their aggregation ability. The anti-GBS activity may be due to non-proteinaceous components of lactobacilli cell wall.